2022
DOI: 10.3847/1538-4357/ac5d46
|View full text |Cite
|
Sign up to set email alerts
|

SolO/EUI Observations of Ubiquitous Fine-scale Bright Dots in an Emerging Flux Region: Comparison with a Bifrost MHD Simulation

Abstract: We report on the presence of numerous tiny bright dots in and around an emerging flux region (an X-ray/coronal bright point) observed with SolO’s EUI/HRIEUV in 174 Å. These dots are roundish and have a diameter of 675 ± 300 km, a lifetime of 50 ± 35 s, and an intensity enhancement of 30% ± 10% above their immediate surroundings. About half of the dots remain isolated during their evolution and move randomly and slowly (<10 km s−1). The other half show extensions, appearing as a small loop or surge/jet, with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 112 publications
3
11
0
Order By: Relevance
“…These jets are of short duration and less than half the length of jets reported in another study based on Hi-C observations by Panesar et al (2019) where the jets had their origin due to photospheric magnetic flux cancellation. These nanojets are of about less than half the length but are of similar widths when compared with microjets observations by Hou et al (2021) and jet-like campfires and EUV dots reported by Panesar et al (2021) and Tiwari et al (2022), respectively, using the Solar Orbiter EUI data. The lifetime of the observed nanojets is on average smaller than the small-scale jet-like features in aforementioned studies.…”
Section: Conclusion and Discussionsupporting
confidence: 78%
“…These jets are of short duration and less than half the length of jets reported in another study based on Hi-C observations by Panesar et al (2019) where the jets had their origin due to photospheric magnetic flux cancellation. These nanojets are of about less than half the length but are of similar widths when compared with microjets observations by Hou et al (2021) and jet-like campfires and EUV dots reported by Panesar et al (2021) and Tiwari et al (2022), respectively, using the Solar Orbiter EUI data. The lifetime of the observed nanojets is on average smaller than the small-scale jet-like features in aforementioned studies.…”
Section: Conclusion and Discussionsupporting
confidence: 78%
“…These observations were made as a part of a technical compression test of HRI EUV , therefore having variable settings. Nonetheless, 60 images are well exposed, unbinned, and compressed at high-quality levels (Panesar et al 2021;Tiwari et al 2022). The HRI EUV events appear 3.22 minutes earlier than the SDO/AIA images because, as mentioned, the Solar Orbiter was closer to the Sun than the SDO.…”
Section: Solar Orbiter/euimentioning
confidence: 89%
“…They occur at the edges of quiet Sun network regions and are driven by the eruption of cool plasma structures. Further, there are several other campfire-like events that were observed by HRI EUV e.g., fine-scale dots in an emerging region (Tiwari et al 2022), plasma jets (Chitta et al 2021), and plasma flows (Mandal et al 2021;Li 2022).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, Berghmans et al (2021) pointed out that the reconnection responsible for campfires appears at the apexes of intersected loops; nevertheless, our results show that it more likely occurs at the legs of loops. Very recently, Tiwari et al (2022) even found some very tiny dot-like EUV brightenings, part of which were identified to be caused by reconnection at a lower height. In short, we support the argument that, despite a shorter duration, the campfires belong to the flare family and that the corresponding scale resides between microflares and nanoflares.…”
Section: Summary and Discussionmentioning
confidence: 99%